The Federal Reserve in times of economic crisis: Paths and choices since 2007 - Sina Rüdiger (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2013)
This paper studies the actions of the U.S. Federal Reserve Bank during the financial crisis from 2007-2012. Whereas the first two parts concentrate on asset bubble theory and the development of the housing bubble, the third part rates the performance of the Federal Reserve during the crisis. The chosen scoring model approach shows that the average performance of five specific measures taken by the Federal Reserve only ranks between fair and good. Comparing Stiglitz (2010) viewpoints with those of the Federal Reserve, this paper analyzes the federal funds rate, the bailout of AIG, the lending to Bear Stearns, the Term Auction Facility and the failure of Lehman Brothers. This paper argues that the resulting decisions were well intentioned but that the outcome was different from expectations because of missing regulations and restrictions. Furthermore, the structure of the Federal Reserve is examined and criticized.
Keywords: E52; E58; 330; Federal Reserve; financial crisis; housing bubble; monetary policy